Genetic Divergence of Maize Hybrids to Drought Tolerance in Response to Pheno-Physiology and Drought Indices Leading to Grain Yield (Journal of the Bangladesh Agricultural University, 2025)
In an effort to identify drought-tolerant varieties, four important maize hybrids were studied to evaluate their genetic divergences in response to pheno-physiology, yield and drought indices under water deficit stress (WDS). The experiment consisted of two factors and was laid out in a split-plot design with three replications. Two water regimes (well watered and water deficit stress) were applied as the main plot treatments and four maize hybrids (BARI hybrid maize-9, BARI hybrid maize-15, BARI hybrid maize-16 and BWMRI hybrid maize-2) were split over water treatments as sub-plot treatments. The interaction impact of water regimes and maize varieties considerably influenced pheno-physiological traits as well as yield traits of maize, where WDS meaningfully declined the investigated physiological and yield attributes at different magnitudes, except the proline content. Among four hybrids, BWMRI hybrid maize-2 was found to perform better with less reduction percentage, whereas BARI hybrid maize-9 showed the lowest performance with more reduction percentage in terms of the studied traits to WDS. BWMRI hybrid maize-2 showed greater aptitude to hold water in the leaf and better steadiness of chlorophyll content and SPAD value of the leaf under stress than the other three varieties. After all, BWMRI hybrid maize-2 produced the maximum grain yield at both well watered and WDS conditions (13.78 t ha-1 and 12.85 t ha-1, respectively) with DSI value 0.78; on the contrary, BARI hybrid maize-9 produced the lowest grain yield (12.21 t ha-1 and 11.02 t ha-1, respectively) with DSI value 1.13. Based on pheno-physiological and yield responses as well as tolerance and susceptibility indices of maize hybrids to WDS, BWMRI hybrid maize-2 was identified as comparatively tolerant and BARI hybrid maize-9 as sensitive, whereas BARI hybrid maize-15 and BARI hybrid maize-16 were found as moderately tolerant to drought.J Bangladesh Agril Univ 23(3): 281–286, 2025